2021
DOI: 10.1002/pen.25829
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy to determine the optimal clamping force based on the clamping force change during injection molding

Abstract: Injection molding machines are widely used to fabricate plastic products with complex geometries and structures. They consist of an injection unit and a clamping unit. To withstand the pressure of the mold cavity, the clamping unit needs a high clamping force to hold the mold halves. Unfortunately, the clamping force is among the overlooked parameters of the injection molding parameters. Setting the clamping force at max is needed in practice to avoid flash defects for most operators. However, excessive clampi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…It was found that when the clamping force difference value is zero, the mold will not separate [ 9 ]. Therefore, the clamping force difference was also monitored to prevent the mold separation.…”
Section: Adaptive Process Control Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that when the clamping force difference value is zero, the mold will not separate [ 9 ]. Therefore, the clamping force difference was also monitored to prevent the mold separation.…”
Section: Adaptive Process Control Systemmentioning
confidence: 99%
“…The method effectively improves the stability of the product weight. Xu [ 9 ] et al mentioned that the product weight is stable when the clamping force shows no peak variation. Huang et al [ 10 ] mentioned that injection speed, V/P switchover point, and first-stage packing pressure settings are highly correlated with the cavity pressure profile and product quality.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum injection volume 133 cm 3 Screw diameter Ø32 mm listed in Table 3. All of the polypropylene used in the experiments have the same density.…”
Section: Maximum Cf 1600 Knmentioning
confidence: 99%
“…Injection molding machines (IMMs) are common equipment to form polymer materials. [1][2][3] More than 30% of plastic parts are molded by the IM process. [4,5] The repeatability accuracy of the part weight is a comprehensive evaluation standard reflecting the performance of an IMM.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed methodology accurately determines an optimal clamping force using just six shots. Yang et al [ 38 ] proposed an experimental method to determine the optimal clamping force by measuring the difference between the clamping force before mold filling and after cooling. The optimal clamping force, according to the authors, corresponds to the moment when the clamping force change becomes zero.…”
Section: Introductionmentioning
confidence: 99%